Chemical Composition, Antioxidant Activity, and Sensory Characterization of Commercial Pomegranate Juices - Sonia Esposto; Gianluca Veneziani; Agnese Taticchi; Stefania Urbani; Roberto Selvaggini; Beatrice Sordini; Luigi Daidone; Giacomo Gironi; Maurizio Servili (MDPI AG, 2021)
We undertook a qualitative and quantitative assessment of the bioactive compounds, volatile substances, sensory profile, and antioxidant activity of eight different commercial pomegranate juices (PJs) differing by cultivation area, processing (from concentrate (CPJ) or not (NCPJ)), and microbial stabilization. Punicalins were the main ellagitannins, whereas the predominant anthocyanin was cyanidin 3,5-diglucoside, followed by cyanidin 3-glucoside. Total phenols, tannins, hydrolyzable tannins, and anthocyanins in the investigated juices ranged from 1379.9 to 3748.8 mg gallic acid equivalent (GAE)/L, 394.8 to 895.2 mg GAE/L, 150.8 to 2374.2 mg ellagic acid/L, and 0 to 281 mg cyanidin 3-glucoside/L, respectively. Antioxidant activity, determined by DPPH•, FRAP, and ABTS, was positively correlated with the total phenolic compounds and hydrolyzable tannins. Alcohols, acids, and furans were the volatile groups that best described the differences between juices. The most abundant volatile compound was 3-Furfural (8.6-879.9 µg/L) in those juices subjected to the concentration process and to high-temperature short-time (HTST) treatment, whereas it was not present in juice subjected to high-pressure processing (HPP). Processing also affected the juices' sensory attributes: NCPJs were characterized by 'red-purple', 'pomegranate fruit', 'fresh fruit', and 'overall intensity' notes, while in CPJs these notes were not revealed or were masked by those related to heat treatment. Our results provide useful information on the importance of extraction methods and on the overall quality of PJ for the food industry.